2001
DOI: 10.1159/000056241
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ‘Functional Relaxation’ in Comparison to Terbutaline and a ‘Placebo Relaxation’ Method in Patients with Acute Asthma

Abstract: Background: ‘Functional relaxation’ (FR) according to Marianne Fuchs is a body-oriented psychotherapy that involves teaching the patient a type of relaxation techniques aimed at maintaining equilibrium of the nervous system. Methods: In order to determine whether the practice of elementary parts of this therapy has an immediate beneficial effect on pulmonary function, a randomized, single-blind, prospective crossover study was done with 21 asthmatics with acute bronchoconstriction. On 3 consecutive days they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
(19 reference statements)
3
22
0
3
Order By: Relevance
“…This study confirms earlier findings showing a positive effect from FR on lung parameters in patients with bronchial asthma [20, 21]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study confirms earlier findings showing a positive effect from FR on lung parameters in patients with bronchial asthma [20, 21]. …”
Section: Discussionsupporting
confidence: 93%
“…Promising results have also been shown in several studies using the technique of functional relaxation (FR), a brief relaxation technique based on the principles of psychodynamic body psychotherapy. In two trials [20, 21] FR led to significant improvements in pulmonary function in asthma patients, with effect sizes comparable to those induced by inhaled β 2 -sympathomimetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the results of earlier trials which indicated that subjects with bronchial asthma could benefit from relaxation techniques [18,19,20]. …”
Section: Discussionsupporting
confidence: 90%
“…Now, it is also known that anxiety and emotional stress exacerbate or predispose to acute and chronic asthma [17]. Subjects with bronchial asthma, including pregnant women, could also probably benefit from relaxation techniques [18,19,20]. One of the most simple and easily learned techniques for relaxation is progressive muscle relaxation (PMR), currently a widely-used procedure that was originally developed by Jacobson in 1939 and which, in the literature, resulted in the greatest effects on behavioral and self-report measures of relaxation [11], cf.…”
Section: Introductionmentioning
confidence: 99%